Comparison between Immunization Routes of Live Attenuated Salmonella Typhimurium Strains Expressing BCSP31, Omp3b, and SOD of Brucella abortus in Murine Model - Kim, Won K.; Moon, Ja Y.; Kim, Suk; Hur, Jin (Frontiers in Microbiology, 2016)
Live, attenuated Salmonella Typhimurium vaccine candidate expressing BCSP31, Omp3b, and SOD proteins of Brucella abortus was constructed. Thirty BALB/c mice were divided equally into three groups, Group A, were intraperitoneally (IP) inoculated with 100 μl of approximately 1.2 × 106 colony-forming units (CFUs)/ml of the Salmonella containing vector only in 100 μl as a control. And groups B and C mice were orally and IP immunized with approximately 1.2 × 109 CFU/ml of the mixture of three delivery strains in 10 μl and IP immunized with approximately 1.2 × 106 CFU/ml of the mixture in 100 μl, respectively. The serum IgG, TNF-α and IFN-γ concentrations in groups B (except Omp3b) and C were significantly higher than those in group A. Following challenge with B. abortus strain 544; challenge strain was detected <103 CFU from the spleen of all mice of group C. These results suggest that IP immunization with the mixture of the vaccine candidate can induce immune responses, and can effectively protect mice against brucellosis.